MENGENAL KEISTMEWAAN AL-QUR’AN SEBAGAI MUKJIZAT RASULULLAH SAW DALAM KAJIAN I’JAZ AL-QUR’AN - virgiawan, luthfi (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
The miracle of the Qur'an (I'jaz Al-Qur'an) is proof of the power and uniqueness of the Qur'an, where its truth is beyond doubt. This study aims to analyze the miracle of the Qur'an through the study of I'jaz Al-Qur'an, so that the extraordinary values contained therein are maintained and not ignored. A qualitative approach based on literature studies was used in this study. Primary data sources are from the Qur'an and secondary data sources from related articles, books, and journals. Data analysis was carried out through descriptive review, interpretation, and understanding of meaning. The results of the study show that I'jaz Al-Qur'an) is clear evidence of the truth of the Islamic message, where its content and structure are able to move the human heart to believe in and accept its teachings. The uniqueness of the Qur'an is also seen in the use of Arabic which has distinctive characteristics such as rich vocabulary, clarity of pronunciation, neat grammatical structure, and its ability to convey profound messages. This language makes it easier to understand the Koran, making it a blessing, life guidance and guidance for Muslims until the end of time, without undergoing any changes.